Evaluating the performance of cultural strategies with fuzzy data envelopment analysis: a case study of ecotourism centers in Mazandaran province - Narges Larijani; Morteza Shafiee; Seyyed Najafi (International Journal of Research in Industrial Engineering)
The increase in the number of tourists around the world has increased the necessity of planning for the promotion and development of tourism in order to minimize the environmental effects of tourism and maximize the social and economic benefits of tourism destinations. According to the current necessity, in this article, the identification and evaluation of the cultural performance of the ecotourism residences of Mazandaran province from the point of view of tourists has been discussed. The data of the present study is from the narratives related to the cultural strategies of the ecotourism centers of Mazandaran province in online social media. Narratives and data were obtained by searching tourism websites. In this article, the efficiency value of 39 ecotourism centers in Mazandaran province of Iran has been obtained with CCR input nature models and ranked with the Andersen-Petersen super-efficiency model. These ecotourism centers were evaluated with three entrances and three exits, and the inputs were the total land area of the ecotourist residence (square meters), the number of rooms in the ecotourism residence, and the maximum capacity of the ecotourism residence (persons). Also, the overall cleanliness of the ecotourism residence, the way of hosting the ecotourism residence personnel and staff, and the services of the ecotourism residence personnel and staff from the point of view of tourists were considered as the outputs of this study. The ranking of Decision-Making Units (DMUs) is also given. And finally, some solutions have been proposed to improve the situation of ineffective ecotourism resorts.